Shear Failure of Bolted Joints considering Mesoscopic Deformation Characteristics of Rock - Yanhui Cheng; Dongliang He; Jianyu Yang (Advances in Civil Engineering)
In rock engineering of the cold region, there are a lot of rock joints. The shear characteristics of joints play a decisive role in the stability of rock engineering in the cold area. In this paper, based on the numerical simulation method of particle flow, reasonable microscopic parameters are selected for the numerical simulation of the direct shear test of bolted joints. The results show that the shear stiffness and contact modulus are linearly and positively correlated. The greater the contact modulus, the greater the residual stress, the better the synergetic effect between rock and bolt, and the more developed the microcrack. The smaller the contact stiffness ratio, the greater the residual stress. The shear stiffness decreases with the increase in the contact stiffness ratio, and the larger the contact stiffness ratio, the slower the shear stiffness decreases, while the shear strength does not change with the contact stiffness ratio. The contact stiffness ratio has a weak effect on the number of cracks in the model. The shear stiffness increases with the increase in the parallel bond modulus, and the shear strength decreases with the increase in the parallel bond modulus. The binding stiffness is independent of the shear stiffness, and the peak shear stress decreases with the increase in the binding stiffness ratio. The greater the bond stiffness ratio, the greater the number of cracks.